(untitled) (Research, Society and Development, 2021)
The objective was to evaluate the autonomic modulation of heart rate in musical stimuli in musicalized (GM) and non-musicalized (GNM) individuals. 96 volunteers were evaluated. Four different songs (M1, M2, M3 and M4) were performed. Data analysis was performed in the time domain using RMSSD (square root of the mean square of the differences between consecutive heart rate variability intervals) and pNN50 (NN50: absolute quantity) indices. (count) of NN intervals that differ by more than 50ms from the previous interval - pNN50: percentage of NN50 in relation to the total amount of NN intervals), and in the frequency domain by low frequency indices - LF (sympathetic activity), high frequency - HF (parasympathetic activity) and LF/HF (sympathetic-vagal balance). Results: GM showed lower parasympathetic activity during exposure to different types of music, regardless of gender (p<0.05). However, during the execution of M3, higher BF values ​​were observed in the female group (p<0.05). In the male group, an increase in the BF band and in the BF/AF ratio was found during the performance of excitatory and sedative music (p<0.05). In GNM, the results were similar between different types of music, confirmed by specific comparison between groups where there were significant differences between them (p<0.05), except in BF during M3, with lower values for GNM. It is concluded that the musical stimulus caused changes in the HRV in the individuals evaluated.